The silent threat: investigating the incidence and clinical characteristics of pre-eclampsia and eclampsia in women from tertiary care hospitals of the Democratic Republic of Congo - Nyakio, Olivier; Cakwira, Hugues; Masimango, Gaston; Kena, Louison; Narayan, Gaurang; Naaz, Farheen; Mugenyi, Nathan; Cyubahiro, Vérité K.; Amani, Toussaint; Balagizi, Fabien; Suvvari, Tarun Kumar; Oduoye, Malik Olatunde; et al. (Annals of Medicine and Surgery, 2024)
Background: Pre-eclampsia and eclampsia are medical conditions that can cause severe complications, such as maternal and foetal morbidity and mortality. This study aimed to assess the incidence and characteristics of pre-eclampsia and eclampsia. Methods: From July 2021 to July 2022, the authors conducted a retrospective, cross-sectional, descriptive study in the Department of Obstetrics and Gynaecology of a tertiary care hospital in the Democratic Republic of the Congo (DR Congo). Out of 123 6total deliveries, 40 patients aged 18–35years with pre-eclampsia and/ or eclampsia with completed attain medical records were studied. Results: In the studied group, 3.23% of women (40 cases) experienced pre-eclampsia or eclampsia, with the majority (75%, 30 cases) occurring before childbirth. Among these,62.5%(25 cases) were ﬁrst-time mothers. The main complications observed in the mothers included HELLP syndrome and placental abruption, whereas their newborns frequently exhibited delayed in-utero growth. Caesarean delivery was the prevalent birthing method, and the treatments most often used for effective management were magnesium sulfate and nicardipine. Conclusion: The research highlights the common occurrence of eclampsia among patients in the DRC and stresses the critical need for prompt detection of hypertensive complications during pregnancy, aiming to reduce negative health impacts on both mothers and their children
Keywords: Eclampsia; Hypertension; Pre-eclampsia; Pregnancy; Women health